MEASURING THE PERCEPTIONS OF WHERE AND WHEN MOST RESIDENTIAL BURGLARIES OCCUR IN THE NEWLANDS EAST POLICING PRECINCT, DURBAN - Nokukhanya Neptune Mbonambi (CV. RADJA PUBLIKA, 2025)
This study examines the spatial and temporal distribution of residential burglaries in the Newlands East Policing Precinct of Durban, South Africa. Understanding the geographic and temporal patterns of crime is essential for developing effective crime prevention strategies and optimizing resource allocation. A qualitative research design was employed, utilizing focus group discussions and semi-structured interviews with 37 participants, including members of the South African Police Services (SAPS), Community Policing Forums (CPFs), local ward councillors, and community members. Findings indicate that burglaries are spatially concentrated in the Newlands West area and exhibit seasonal fluctuations throughout the year. Key contributing factors to burglary prevalence include poverty, inequality, and unemployment, underscoring the socio-economic dimensions of crime in the study area. The research highlights the necessity for a multi-stakeholder approach involving law enforcement, government agencies, and community members to effectively address residential burglaries. This study contributes to the limited empirical research on the spatial and temporal aspects of residential burglary in South Africa. It emphasizes the importance of targeted crime prevention measures and strategic policing interventions to mitigate burglary rates. The findings support the need for future research to further explore the socio-economic drivers of crime and the effectiveness of various crime prevention initiatives.